Austerity Ireland : the failure of Irish capitalism - Allen, Kieran, 1954- (Pluto Press, 2013)
Ireland has been marketed as the poster boy of EU austerity. EU elites and neoliberal commentators claim that the country's ability to suffer economic pain will attract investors and generate a recovery. In this book Kieran Allen challenges this official narrative and argues that the Irish state's response to the crash has primarily been designed to protect economic privilege.